Genetic potential of Kazakh White-headed and Hereford breeds for beef production in Purebred farms and crossbreeding - ROZA IBRAYEVA; KUAT NURGAZY; KALIYA SATIYEVA; GULZAT GABIT; ORYNGUL MUKHAMETZHANOVA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ibrayeva R, Nurgazy K, Satiyeva K, Gabit G, Mukhametzhanova O. 2025. Genetic potential of Kazakh White-headed and Hereford breeds for beef production in Purebred farms and crossbreeding. Biodiversitas 26: 761-769. Kazakhstan is experiencing essential growth in the livestock sector, with the production of environmentally friendly products serving as a key competitive advantage for the nation. Our study analyzed the meat productivity indices of the Kazakh White-headed and Hereford breeds, along with their hybrids. The investigation focused on assessing the meat quality of Kazakh White-headed and Hereford bulls in different genotype combinations by comparing key meat productivity indices. The meat from the controlled slaughter of test bulls complied with Category I requirements. Carcass weights of Hereford bulls surpassed those of the Kazakh White-headed breed by 42.9 kg (18.1%, P?0.05) and exceeded those of crossbreed bulls by 9.0 kg (3.3%, P?0.05). The Kazakh White-headed breed demonstrated a higher yield of internal fat: internal fat yield varied on average from 2.5% to 3.2% (15 month aged bulls) that depended on the breed: Kazakh White-headed ?3.2%, Hereford ?2.5%, and crossed bulls ? of 2.7%. However, in terms of flesh content, Kazakh White-headed bulls were 43.2 kg (22.5%, P?0.05) lighter than Hereford bulls, and crossbreed bulls were 8.1 kg (3.6%, P?0.05) lighter. In analyzing flesh yield, Kazakh White-headed bulls fell short by 2.4 kg (2.9%) compared to Hereford bulls, which were marginally lower by 0.1 kg (0.1%) compared to crossbreed bulls of the same age. The protein-fat ratio was determined to be 1:0.65 in Kazakh White-headed bulls and 1:0.64 in both Hereford and crossbreed bulls. Profitability was 22% for the Kazakh White-headed breed, 43% for the Hereford breed, and 39% for the crosses of the White-headed and Hereford breeds.